Assessment of Public-Private Partnerships in Enhancing Water Transportation in Lagos State - Elegbede Victor John (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
This study explores the role of Public-Private Partnerships (PPPs) in improving urban water transportation efficiency and sustainability in Lagos State. As Lagos faces severe transportation challenges due to over-reliance on road transport, this research investigates the potential of PPPs to mitigate congestion, enhance infrastructure, and reduce environmental impacts. Using a mixed-methods approach, the study integrates both quantitative and qualitative data collected from 175 respondents, including ferry commuters, Lagos State Waterways Authority (LASWA) officials, and private ferry operators. The research captures perceptions of efficiency, affordability, safety, and sustainability in the current water transport system. Findings reveal strong awareness and support for PPP involvement, with significant recognition of the benefits, including better infrastructure and more reliable services. However, concerns about fare increases and weak regulation remain. Data analysis indicates that PPPs have the potential to offer a sustainable solution, provided there is adequate regulation, private sector involvement, and a balance between profitability and public interest. The study highlights the need for tailored PPP frameworks in Lagos to address specific challenges, including regulatory enforcement and equity. The findings contribute to the ongoing debate on sustainable urban mobility and offer policy recommendations for integrating water transport into a broader multimodal transport system for Lagos and other African megacities.